2014
DOI: 10.1007/s40097-014-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of nanoarchitectures from fatty acid derivatives of 2,6-diaminopyridine and 2-aminopyridine

Abstract: The self-assembling property of lipids makes it an important building block in the field of supramolecular nanoarchitectures with a variety of applications in chemistry, biochemistry, materials science and medicine. We report here, the synthesis and formation of variety of nanostructures such as nanosheets, nanofibers and nanotubes of fatty acid derivatives of 2,6-diaminopyridine and 2-aminopyridine. These molecules possess a saturated or unsaturated long alkyl-chain group as the self-assembling unit. The mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The peak at 33 ppm is the evidence of the formation of the products obtained by the Michael addition. A peak observed at 175 ppm is related to the carbonyl carbon atoms of amide group formed with the amidation reaction with 2,6-diaminopyridine, which present the peaks at 104, 113, 140, and 157 ppm . The materials with different generations of PAMPy adsorb CO 2 from air forming carbamate (Figure II) in the same manner as NH 2 -talc, causing the appearance of the signal at 165 ppm. , …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The peak at 33 ppm is the evidence of the formation of the products obtained by the Michael addition. A peak observed at 175 ppm is related to the carbonyl carbon atoms of amide group formed with the amidation reaction with 2,6-diaminopyridine, which present the peaks at 104, 113, 140, and 157 ppm . The materials with different generations of PAMPy adsorb CO 2 from air forming carbamate (Figure II) in the same manner as NH 2 -talc, causing the appearance of the signal at 165 ppm. , …”
Section: Resultsmentioning
confidence: 96%
“…A peak observed at 175 ppm is related to the carbonyl carbon atoms of amide group formed with the amidation reaction with 2,6-diaminopyridine, which present the peaks at 104, 113, 140, and 157 ppm. 41 The materials with different generations of PAMPy adsorb CO 2 from air forming carbamate (Figure 3II) in the same manner as NH 2 -talc, causing the appearance of the signal at 165 ppm. 50,51 Dendron−iodine charge-transfer complexes linked to organotalc lamella were obtained by adsorption of vapor of iodine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrate the importance of supramolecular interactions in governing the structural features of precision polymers incorporating regularly spaced functional groups in linear polyethylene. It is demonstrated that the used 2,6-diaminopyridine (DAP) group capable of introducing interactions via H-bonding 22 or pi-stacking 23 can stabilize different layered superstructures containing up to three monomeric repeating units (refer Scheme 1) along the chain axis. Varying the DAP to methylene units ratio (methylene spacer length) allows for tuning the nature of the layered structures.…”
mentioning
confidence: 99%